2012
DOI: 10.1186/1476-511x-11-70
|View full text |Cite
|
Sign up to set email alerts
|

Short term effects of different omega-3 fatty acid formulation on lipid metabolism in mice fed high or low fat diet

Abstract: BackgroundBioactivities of Docosahexaenoic acid (DHA) and Eicosapentaenoic acid (EPA) depend on their chemical forms. The present study was to investigate short term effects of triglyceride (TG), ethyl ester (EE), free fatty acid (FFA) and phospholipid (PL) forms of omega-3 fatty acid (FA) on lipid metabolism in mice, fed high fat or low fat diet.MethodMale Balb/c mice were fed with 0.7% different Omega-3 fatty acid formulation: DHA bound free fatty acid (DHA-FFA), DHA bound triglyceride (DHA-TG), DHA bound et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…In addition to n-3 PUFA compositions, ethyl esters and triglycerides are two main forms of commercial fish oil available in the market [54]. The apparent bioavailability is considered to be the lowest for the ethyl ester form and the highest for the free fatty acid form [55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to n-3 PUFA compositions, ethyl esters and triglycerides are two main forms of commercial fish oil available in the market [54]. The apparent bioavailability is considered to be the lowest for the ethyl ester form and the highest for the free fatty acid form [55].…”
Section: Discussionmentioning
confidence: 99%
“…As essential constituents of the cell membrane, phospholipids, such as phosphatidylcholine and phosphatidylethanolamine, can influence the surface composition of fat droplets thus facilitating their hydrolysis and digestion 34 . It is believed that these surface-active agents are good bioactive substances for preventing hypertriglyceridemia 7 . When PUFAs are present at the sn-2 position, the PUFAs can maintain its effect in the body rather than entering the circulation to be oxidized and separated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of dietary fat content on the bioavailability of DHA has not been reported. Tang s study 7 with low dosage omega-3 PUFA treatments suggested that both total dietary fat content and the molecular form of omega-3 PUFA affected the lipid metabolism of mice in a short time. DHA-PL was considered the most effective DHA form for decreasing hepatic and serum TC and TG levels; it contributed to increasing omega-3 concentration in the liver and brain.…”
Section: Introductionmentioning
confidence: 99%
“…Shirouchi et al investigated the effect of n-3 PUFAs EPA,12.0 ; DHA, 28.1 containing PC on obesity-related disorders, which also showed that EPA and DHA levels were markedly increased by n-3 PUFAs-PC diet, compared with the egg-PC diet 47 . Our previous study suggested that the PL form of n-3 PUFAs the ratio of DHA to EPA, 2.6:1 increased DHA concentration in liver 7,11 . Furthermore, rats orally administered with DHA-PC and DHA-PS containing water for 4 days showed that DHA level in the liver, serum and brain was similar between the two groups 48 .…”
Section: Fatty Acidmentioning
confidence: 99%